Pengukuran Acuan Terpadu (PAT) dalam Mengukur Kompetensi dalam bidang Teknik Sipil - Arthur, Riyan (Jurnal Pensil : Pendidikan Teknik Sipil, 2014)
As is known the curriculum in 2013 , oriented competence therefore already be fitting if the measurement and assessment system using Reference Asessment Standard (PAP) . However, the main vocational science in civil engineering will be less about the target if the measurement system is only focused on cognitive or psychomotor without considering the affective domain.The integration of a unified standard reference measurement in the evaluation of the scope of learning which includes cognitive, affective and psychomotor important . Therefore , it is necessary formulate it provisionally into an integrated system through a fair weighting of each realm . Educational institutions providing education in the field of civil engineering , formulation should have a high weight is covering psychomotor skills in work may be given a weighting of 40 % , which includes the affective attitude , responsibility , and discipline 30 % and cognitive science covering 30 % adjusted to the level of competency that must be mastered